2016
DOI: 10.1016/j.bone.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte-directed bone demineralization along canaliculi

Abstract: The mammalian skeleton stores calcium and phosphate ions in bone matrix. Osteocytes in osteocyte lacunae extend numerous dendrites into canaliculi less than a micron in diameter and which are distributed throughout bone matrix. Although osteoclasts are the primary bone-resorbing cells, osteocytes also reportedly dissolve hydroxyapatite at peri-lacunar bone matrix. However, robust three-dimensional evidence for peri-canalicular bone mineral dissolution has been lacking. Here we applied a previously reported Tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 38 publications
0
84
1
3
Order By: Relevance
“…Calcium and phosphates along the LCS walls appear to be more labile and readily exchanged with the bone fluid. (59) Nango and colleagues (31) recently confirmed the existence of a small zone of mineral on canalicular walls that is rapidly mobilized in lactation and other stress states. Together, these data indicate that there are no changes in the overall mineral content of bone matrix after lactation in mouse, and so bulk changes in mineralization do not contribute to the changes in bone tissue material properties seen with lactation and recovery.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Calcium and phosphates along the LCS walls appear to be more labile and readily exchanged with the bone fluid. (59) Nango and colleagues (31) recently confirmed the existence of a small zone of mineral on canalicular walls that is rapidly mobilized in lactation and other stress states. Together, these data indicate that there are no changes in the overall mineral content of bone matrix after lactation in mouse, and so bulk changes in mineralization do not contribute to the changes in bone tissue material properties seen with lactation and recovery.…”
Section: Discussionmentioning
confidence: 96%
“…The need to release mineral, rather than matrix constituents, from bone has long been considered the primary driver of osteocytic osteolysis, (6,8,10,31,53,6367) and presumably such rapid mineral removal occurs through acidification of the fluid in the LCS. Data to support LCS acidification during lactation are lacking, but the ability of osteocytes to acidify their local microenvironment was recently demonstrated in sciatic neurectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are data suggesting that osteocytes remodel its lacunae and canaliculae [36, 37], which involves similar mechanisms that osteoclasts use for resorbing bone (i.e., acidification, demineralization, and collagen degradation). The subsequent formation process in the osteocyte lacuna remains elusive; however, we suggest that this process could be mediated by TRAP, instead of BALP, in controlling the inhibitory effect of PPi and/or OPN.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Qing et al 52 reported that tartrate-resistant acid phosphatase and cathepsin K were involved in osteocytic osteolysis. They also reported that no osteocytic remodeling was observed with experimental unloading.…”
Section: Discussionmentioning
confidence: 99%